436Food addiction, mental health and substance-use during a transition period: Data from 6, 700 Australian 12/13-year-olds. (2nd September 2021) - Smout, Scarlett; Gardner, Lauren; Newton, Nicola; Champion, Katrina; Chapman, Cath; Slade, Tim; Sunderland, Matthew; Thornton, Louise; Kay-Lambkin, Frances; Teesson, Maree
Abstract: Background: Early adolescence is a challenging transition period where mental ill-health and experimentation with alcohol and tobacco often increases. Some foods and eating behaviours can be addictive in a way that is comparable to addictive substances. Few studies have examined the prevalence of food addiction in young people, and none have measured it with mental ill-health and substance-use. Methods: 6, 700 Year 7 students across NSW, WA and QLD completed the baseline questionnaire for "Health4Life" (Mage =12.7±0.5, 49%F). The prevalence of, and associations between, food addiction (YFAS-C), anxiety (PROMIS-A), depression (PHQ-A), psychological distress (K6), discretionary food/drink intake (SPANS) and alcohol and tobacco use were examined. Results: Respondents who met diagnostic criteria for food addiction (5.2%, n = 272) were significantly more likely to screen positively for anxiety (X 2 3 =315.4, P < 0.001), probable major depression (X 2 1 =299.9, P < 0.001) and psychological distress at levels of serious mental illness (X 2 1 =238.885, P < 0.001). They were also significantly more likely to have consumed a full standard drink and smoked tobacco in the past 6-months (X 2 1 =53.8, P < 0.001 and X 2 1 =29.7, P < 0.001, respectively) and to consume high amounts of sugar-sweetened beverages (X 2 1 =15.2, P < 0.001), discretionary foods (X 2 2 =26.4, P < 0.001) and energy drinks (X 2 5 =28.4, P < 0.001). Relative risks ranged 1.29-4.35. Conclusions: Findings suggest a strong link between food addiction, substance use, discretionary food and drink consumption and mental ill-health in early adolescence. Further analysis will model multivariable relationships whilst controlling for affluence, BMI and gender. Key messages: Links between food addiction, substance use and mental ill-health are found in the largest sample of adolescents screened for these variables worldwide.